Energy sustainability under the framework of telecoupling. (1st July 2016) - Fang, Baling; Tan, Yi; Li, Canbing; Cao, Yijia; Liu, Jianguo; Schweizer, Pia-Johanna; Shi, Haiqing; Zhou, Bin; Chen, Hao; Hu, Zhuangli
Abstract: Energy systems, which include energy production, conversion, transportation, distribution and utilization, are key infrastructures in modern society. Interactions among energy systems are generally studied under the framework of energy trade. Although such studies have generated important insights, there are limitations. Many distant interactions (e.g. those due to the Fukushima nuclear crisis) are not in the form of trade, but affect energy sustainability. Even when distant interactions are related to energy trade, they are not systematically analyzed. Environmental impacts of trade are often not integrated with economic analysis of trade. In this paper, to identify and fill important knowledge gaps, we apply an integrated framework of telecoupling (socioeconomic and environmental interactions over distances). The framework of telecoupling, which is more comprehensive and cross-disciplinary than the energy trade framework, is a useful theoretical and methodological tool for analyzing distant interactions among coupled human and natural systems (including energy systems). Telecouplings widely exist in energy systems with various forms and link energy sustainability of different countries closely, so we proposed some methods for energy sustainability analysis under the framework of telecoupling. From the aspect of causes, a method is proposed to judge whether the telecoupling driven by economic factors is conducive to energy sustainability. From the aspect of effects, a method is proposed to assess whether an event is conducive to energy sustainability. The telecoupling framework presents opportunities for more profound and comprehensive understanding of energy sustainability. Highlights: A new perspective to study energy sustainability under telecoupling is proposed. Methods for assessing the causes and effects of energy sustainability are proposed. Some specific examples of telecoupling in the energy systems are demonstrated.